ANALISIS INTERVENSI FISKAL TERHADAP KEMISKINAN (STUDI KASUS DANA DESA PULAU KALIMANTAN) - LUBIS, M. ZAKY MUBARAK; DAHRAINI, APRIAN SUBHAN (IAIN Batusangkar, 2018)
ABSTRACTOne of the government's strategies to help the village become independent and autonomous by giving the allocation of village funds. The funds allocated for the rural area, and expected to support the implementation of the people?s empowerment and the rural development, so that funds can improve the people?s prosperity. Furthermore, the aims of this study to look at the influence of Fiscal Intervention which are representated by Village Fund, Village Fund Allocation, and part of Local Earning and Retribution toward Poverty which is representated by Poverty Rate of Residences/Cities in Kalimantan Island during 2015-2017. This research used quantitative descriptive approach with Panel Data Model. The result showed of Fixed Effect Model regression that, Village Fund, Village Fund Allocation, and part of Local Earning and Retribution have have negative significant influence at Poverty Rate for 47 Residences/Cities in Kalimantan Island.